Characterization of DAG Binding to TRPC Channels by Target-Dependent cis–trans Isomerization of OptoDArG - Hazel Erkan-Candag; Denis Krivic; Mathias A. F. Gsell; Mina Aleksanyan; Thomas Stockner; Rumiana Dimova; Oleksandra Tiapko; Klaus Groschner (Biomolecules, 2022)
Azobenzene-based photochromic lipids are valuable probes for the analysis of ion channel–lipid interactions. Rapid photoisomerization of these molecules enables the analysis of lipid gating kinetics and provides information on lipid sensing. Thermal relaxation of the metastable cis conformation to the trans conformation of azobenzene photolipids is rather slow in the dark and may be modified by ligand–protein interactions. Cis photolipid-induced changes in pure lipid membranes as visualized from the morphological response of giant unilamellar vesicles indicated that thermal cis–trans isomerization of both PhoDAG-1 and OptoDArG is essentially slow in the lipid bilayer environment. While the currents activated by cis PhoDAG remained stable upon termination of UV light exposure (dark, UV-OFF), cis OptoDArG-induced TRPC3/6/7 activity displayed a striking isoform-dependent exponential decay. The deactivation kinetics of cis OptoDArG-induced currents in the dark was sensitive to mutations in the L2 lipid coordination site of TRPC channels. We conclude that the binding of cis OptoDArG to TRPC channels promotes transition of cis OptoDArG to the trans conformation. This process is suggested to provide valuable information on DAG–ion channel interactions and may enable highly selective photopharmacological interventions.